DENTOALVEOLAR TRAUMA IN WOMEN VICTIMS OF DOMESTIC VIOLENCE: CLINICAL AND LEGAL IMPLICATIONS (REMUNOM, 2026)
Domestic violence against women represents a significant public health issue, with substantial impacts on the physical, psychological, and social integrity of victims, particularly highlighting injuries in the maxillofacial region as one of its most frequent manifestations. In this context, the present study aims to analyze dentoalveolar trauma in women victims of domestic violence, emphasizing its clinical and legal implications, as well as the role of the dentist in identifying, documenting, and managing such cases. This is a qualitative, descriptive, and analytical literature review, based on scientific articles published between 2020 and 2025, selected from academic databases according to relevance and full-text availability criteria. The findings indicate that dentoalveolar injuries, such as fractures, luxations, and avulsions, show high incidence in contexts of violence, especially in the anterior region of the face, constituting important clinical indicators of aggression. Furthermore, the study highlights the importance of the dentist's role in the early identification of violence, in the preparation of detailed clinical records, and in the production of technical evidence that may support legal proceedings. It is concluded that an interdisciplinary approach between dentistry and law is essential to address domestic violence, requiring improved professional training and the strengthening of clinical and legal practices aimed at protecting women